Acute TBK1/IKK-ε Inhibition Enhances the Generation of Disease-Associated Microglia-Like Phenotype Upon Cortical Stab-Wound Injury - Rehman, Rida; Tar, Lilla; Olamide, Adeyemi Jubril; Li, Zhenghui; Kassubek, Jan; Böckers, Tobias; Weishaupt, Jochen; Ludolph, Albert; Wiesner, Diana; Roselli, Francesco (Frontiers in Aging Neuroscience, 2021)
Traumatic brain injury has a poorer prognosis in elderly patients, possibly because of the enhanced inflammatory response characteristic of advanced age, known as “inflammaging”. Recently, reduced activation of the Tbk1 pathway has been linked to age-associated neurodegeneration and neuroinflammation. Here we investigated how the blockade of Tbk1 by the small molecule Amlexanox could modify the microglial and immune response to cortical stab-wound injury in mice. We demonstrated that Tbk1 inhibition resulted in a massive expansion of microglial cells characterized by the TMEM119+/CD11c+ phenotype, expressing high levels of CD68 and CD317, and with the upregulation of Cst7a, Prgn and Ccl4 and the downregulation of Trem119 and P2yr12, thus a profile close to Disease-Associated Microglia (DAM, a subset of activated microglia abundant in Alzheimer Disease and other neurodegenerative conditions). Furthermore, Tbk1 inhibition increased the infiltration of CD3+ lymphocytes, CD169+ macrophages and CD11c+/CD169+ cells. The enhanced immune response was associated with increased expression of Il-33, Ifn-g, Il-17, and Il-19. This upsurge in the response to the stab wound was associated with the expanded astroglial scars and increased deposition of chondroitin-sulfate proteoglycans at 7 dpi. Thus, Tbk1 blockade results in a massive expansion of microglial cells with a phenotype resembling DAM and with the substantial enhancement of neuroinflammatory responses. In this context, in contrast to what was hypothesized for Alzheimer's Disease, the induction of DAM is associated with a detrimental outcome, with larger injury-related glial scars. Thus, the Tbk1 pathway is critical to repress neuroinflammation upon stab-wound injury and Tbk1 inhibitors may provide an innovative approach to investigate the consequences of DAM induction.